Developing Ethnomathematics-Based Outdoor PBL Materials for Mathematical Problem Solving - Amidi Amidi; Zaenuri Zaenuri; Scolastika Mariani (Jurnal Pendidikan MIPA, 2026)
This study was motivated by the limited use of mathematics teaching materials that facilitate students’ mathematical problem-solving abilities through contextual learning experiences. As a result, students often have difficulty understanding concepts and solving mathematical problems systematically. This research aimed to develop comparative and scale teaching materials with ethnomathematical nuance, integrated with Problem-Based Learning (PBL) and outdoor learning strategies; to determine the feasibility and readability of the developed materials; and to describe students’ mathematical problem-solving abilities after the implementation of the teaching materials. This study employed a Research and Development (R&D) method using the 4D development model, which consisted of define, design, and develop stages. The research subjects were 30 seventh-grade students (N = 30) at one of the junior high schools in Semarang Regency. Data were collected through expert validation sheets, readability questionnaires, mathematical problem-solving tests, and documentation. The feasibility test involved two mathematics education lecturers and two junior high school mathematics teachers. The findings showed that the developed teaching materials were deemed feasible based on expert validation results across content, presentation, and language. The readability test also indicated that the teaching materials were easy for students to understand. Furthermore, the pretest and posttest analysis showed an improvement in students’ mathematical problem-solving abilities, with an N-gain score of 0.66, placing it in the medium category. Most students’ posttest scores were higher than their pretest scores after learning using the developed teaching materials. Therefore, the developed teaching materials demonstrated validity and practicality and showed potential to support improvements in students’ mathematical problem-solving abilities through contextual ethnomathematics-based learning activities. Keywords: mathematics problem-solving, ethnomathematics, outdoor learning, PBL.